2017
DOI: 10.1038/s41598-017-00353-y
|View full text |Cite
|
Sign up to set email alerts
|

A robust empirical seasonal prediction of winter NAO and surface climate

Abstract: A key determinant of winter weather and climate in Europe and North America is the North Atlantic Oscillation (NAO), the dominant mode of atmospheric variability in the Atlantic domain. Skilful seasonal forecasting of the surface climate in both Europe and North America is reflected largely in how accurately models can predict the NAO. Most dynamical models, however, have limited skill in seasonal forecasts of the winter NAO. A new empirical model is proposed for the seasonal forecast of the winter NAO that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 51 publications
6
132
0
2
Order By: Relevance
“…However, there is also evidence that other climate components such as the stratosphere, sea ice, and local and remote air‐sea interactions affect the NAO variability. Recently, it has been shown that these subcomponents can be used to enhance the NAO prediction (Dobrynin et al, ; Hall et al, ; Wang et al, ). To examine the total effect of the higher‐resolution model version, the contributions of these climate subsystems on the NAO variability need to be considered; this is not done here.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that other climate components such as the stratosphere, sea ice, and local and remote air‐sea interactions affect the NAO variability. Recently, it has been shown that these subcomponents can be used to enhance the NAO prediction (Dobrynin et al, ; Hall et al, ; Wang et al, ). To examine the total effect of the higher‐resolution model version, the contributions of these climate subsystems on the NAO variability need to be considered; this is not done here.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of these months was primarily motivated by previous studies suggesting links between September and October sea ice and the winter atmospheric circulation (Francis et al, 2009;Hall et al, 2017;Wang et al, 2017), but was also constrained by what was achievable using the albedo reduction method. This results in yearround reduction in SIE highly similar to that projected in the 2C ensemble.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…Autumn Arctic sea ice has been shown to be a potential predictor of the winter NAO in both dynamical (Scaife et al, 2014) and statistical forecasts (Hall et al, 2017;Wang et al, 2017). This has implications for understanding the underlying physical mechanisms and for seasonal predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Hall et al ., ; Smith et al ., ), with the possibility that forecasts can be extended to over a year ahead (Dunstone et al ., ). Recent statistical forecasts of the winter NAO provide further evidence for this link (Hall et al ., ; Wang et al ., ). A reliable seasonal forecast of the winter NAO will indicate the weather patterns expected in the UK during the upcoming winter months, which is invaluable to planners and decision makers.…”
Section: Introductionmentioning
confidence: 97%